Continuous synthesis of ginkgolide B derivatives in a micro-flow system. Issue 11 (16th March 2016) - Qin, Yinlin; He, Wei; Su, Mei; Fang, Zheng; Gu, Jiajia; Ouyang, Pingkai; Guo, Kai
Graphical abstract: Abstract: In this study, etherification process of ginkgolide B in a micro-flow system was investigated. With calcium carbonate as an acid-binding agent, the optimal result was obtained in such conditions: residence time 3 min, temperature 85 °C, molar ratio of ginkgolide B to dimethylamino ethyl chloride hydrochloride 1:2, molar ratio of ginkgolide B to potassium iodide 1:0.2, and molar ratio of ginkgolide B to calcium carbonate 1:2.5. Meanwhile, this novel process in MFS could proceed well for the etherification reaction between ginkgolide B and other halides, to afford the target products in moderate yields. Besides, salification reaction was conducted in a valve assisted micromixer by reacting dimethylaminoethyl ginkgolide B with methane sulfonic acid. Compared with conventional drugs, enhanced bioavailability was obtained when nano-scale drugs were dosed.